International Scholar Mobility to United States Claws Back from Its Pandemic Plunge - Glass, Chris (International Higher Education, 2024)
Geopolitics are reshaping global science as the United States decouples from China and aligns with India. Scholar mobility from South Korea maintains resilience while mobility from Brazil continues its steady ascent. Postpandemic scholar mobility to the United States lingers at levels from 15 years ago. As emerging powers expand academic partnerships and research activity, adaptation imperatives loom for the United States to retain leadership in science.